2023
DOI: 10.3389/fpls.2023.1119162
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic analysis and functional characterization reveals that the class III peroxidase gene TaPRX-2A regulates drought stress tolerance in transgenic wheat

Abstract: Drought is a major abiotic stress that reduces crop yields and quality worldwide. Although some genes involved in the response to drought stress have been identified, a more in-depth understanding of the mechanisms underlying wheat tolerance to drought is needed for the control of drought tolerance. Here, we evaluated the drought tolerance of 15 wheat cultivars and measured their physiological–biochemical parameters. Our data showed that the drought tolerance of the resistant wheat cultivars was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
(62 reference statements)
0
0
0
Order By: Relevance
“…Under drought stress, the ROS content in plants increases significantly, leading to oxidative damage to cells [ 5 ]. POD, SOD, and CAT are essential in the maintenance of cellular ROS homeostasis [ 9 ]. The results of the present study showed that POD, SOD, and CAT activities in both asparagus varieties under drought stress increased significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under drought stress, the ROS content in plants increases significantly, leading to oxidative damage to cells [ 5 ]. POD, SOD, and CAT are essential in the maintenance of cellular ROS homeostasis [ 9 ]. The results of the present study showed that POD, SOD, and CAT activities in both asparagus varieties under drought stress increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Drought stress disrupts the balance of ROS metabolism in plants and triggers oxidative stress reactions [ 5 ]. Catalase (CAT), peroxidase (POD), and superoxide dismutase (SOD) are essential in ROS scavenging [ 9 ]. In plants, nonenzymatic defense antioxidants, such as ascorbic acid and glutathione, effectively and efficiently scavenge ROS and enhance redox sensing and signaling [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peroxiredoxins (Prxs) are enzymes that act as antioxidants [30] . To understand how Prxs function in cancer, Lee et al [31] used the DCF-DA fluorescence probe to detect the impact of Prxs on ROS levels in Ca9.22 and OSCC cell lines.…”
Section: Other Applicationsmentioning
confidence: 99%
“…In Arabidopsis, drought-escape-induced early flowering is associated with the phloem tissue transport of the florigen FT protein from the leaves to the shoot apical meristems [62]. Biochemically, it is manifested in the high expression of some drought resistance genes that positively increase the content of amino acids and sugars in plants (such as proline and trehalose), the enhanced activity of antioxidant-related enzymes, and inhibition of the activity of enzymes involved in degradation pathways to ensure that normal metabolic homeostasis is maintained under drought stress condition [63]. ROS, including superoxide radicals (O 2 − ), hydrogen peroxide (H 2 O 2 ), and hydroxyl radicals (OH − ), regulate plant growth and development at lower concentrations [64,65].…”
Section: Perception and Coping Strategies Of Drought Stressmentioning
confidence: 99%